On the reasons of tightening the policy of the Russian Empire in the North Caucasus in the first third of the XIX century - E. V. Kuznetsova (Гуманитарные и юридические исследования)
Caucasus in the first decades of the 19th century, and how it gradually became tougher, and violent actions became the main argument in relations with local peoples. It was explained by disappointment in the ability of the highlanders to comply with the peace agreements reached and to abandon raids directed against Russian subjects. The author supposes the change in the geopolitical situation after the annexation of Georgia to Russia forced to accelerate the process of spreading the legal system of the empire to the mountain communities, which caused fierce resistance from the natives who did not want to renounce their traditions. In turn, the tsarist administration was not inclined to further delay the indefinite status of new subjects, who were formally considered the same people subject to the sovereign, like the rest of the inhabitants of Russia. The situation was aggravated by confessional confrontation, which made it possible to ideologically substantiate the hostility of the opposing side by its other religious preferences. It was supposed to crush the resistance forces with the help of the army and, by establishing a blockade, force the highlanders to stop the armed struggle. The supporters of such methods were very bright and talented generals P.D. Tsitsianov, A.P. Ermolov. They carried out incursions deep into mountain territories, built a line of fortresses, with the help of which they tried to stop the attacks of enemy units on Russian settlements. But, as experience has shown, it was not possible to achieve the expected result. Mountain societies increasingly consolidated and jointly tried to oppose the imperial authorities as a threat to their way of life. The available forces and means were clearly insufficient to subjugate societies that were accustomed to military hardships and knew how to steadfastly manage with a minimum of material wealth.